2016
DOI: 10.3344/kjp.2017.30.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applying nerve blocks to prevent postherpetic neuralgia in patients with acute herpes zoster: a systematic review and meta-analysis

Abstract: BackgroundPostherpetic neuralgia (PHN) is a common and painful complication of acute herpes zoster. In some cases, it is refractory to medical treatment. Preventing its occurrence is an important issue. We hypothesized that applying nerve blocks during the acute phase of herpes zoster could reduce PHN incidence by attenuating central sensitization and minimizing nerve damage and the anti-inflammatory effects of local anesthetics and steroids.MethodsThis systematic review and meta-analysis evaluates the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 39 publications
3
78
0
Order By: Relevance
“…PHN is a ubiquitous sequelae after HZ infection that severely affects patient quality of life 32 . To date, the mechanism involved in the development of PHN remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PHN is a ubiquitous sequelae after HZ infection that severely affects patient quality of life 32 . To date, the mechanism involved in the development of PHN remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, active treatment before the nerve damage occurs can help prevent PHN and control pain. A recent meta-analysis reported that CEI in the acute phase of HZ is effective in controlling pain and preventing PHN [14]. The rationale behind using CEI to manage acute HZ pain and prevent PHN is that the interruption of afferent pain stimuli to the central nervous system and the improved blood flow to nerve tissue will minimize neural damage and reduce pain to the patient by blocking sympathetic nerves [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proactive treatment before nerve injury can help prevent PHN. According to a recent meta-analysis, continuous epidural infusion in acute herpes zoster is effective in preventing PHN [9]. The rationale behind the application of epidural blocks to control acute herpes zoster pain and prevent PHN is that the discontinued delivery of an invasive afferent stimulus to the central nervous system and improved flow of blood to the subjects' nerve tissue will minimize neural damage and reduce sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural, sympathetic, and paravertebral blocks are considered active treatments for acute episodes of herpes zoster. For acute herpes zoster, continuous epidural infusion is commonly used in clinical settings and is reported to reduce the likelihood of transition to PHN via pain control [8][9][10]. For conventional continuous epidural infusion, the location of the epidural catheter is confirmed by injecting a contrast agent at the suspected epidural level, which is identified based on the site of rash or pain.…”
Section: Introductionmentioning
confidence: 99%